(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Geometric constructions serve as the basis for all technical drawings. The goal of geometric making is to construct precisely designed flat geometric shapes, from squares, triangles and three-dimensional cylinders to complex irregular curves and ellipses. These structures are usually produced without the aid of a scale, but rather with simple drafting tools. Engineers, designers and draftsmen regularly use the principles of plane geometry in the production of geometric constructions in their work. The process involved in the production of geometric structures requires a basic understanding of plane geometry. Mastering geometric design skills requires precision and the correct use of drawing tools. When developing geometric structures, it is important that the drafting tools are in good condition. A small error or inaccuracy in solving a geometric problem can lead to a serious error in the final construction. There are a number of basic geometrical constructions that the student should be familiar with. First, the student should learn how to develop different geometric shapes in each drawing, then follow the basic sequence.